Effects of pedal rate and power output on cycling kinematics - Bessot, N. (Movement & Sport Sciences - Science & Motricité, 2018)
The aim of this study was to examine the effect of changes in pedal rate and power output in the cycling kinematics of endurance cyclists. Nine male competitive cyclists performed 16 submaximal effort trials of 4 minutes` duration on a cycle ergometer. Power output was imposed at 50, 100, 150, and 200 W successively for each pedal rate studied (45, 70, 95, 120 rev · min-1). The ankle, knee and hip flexion/extension, and pedal angle (pedal axis/malleolus medialis compared to the horizontal) were analysed. We observed an increase of mean pedal angle and a decrease of magnitude in pedal mobilisation when pedal rate increased or power output decreased. The mean pedal angle recorded during a crank cycle seems to depend on pedal load (power/pedal rate ratio). The supposed effect of pedal rate, power and pedal load on pedal angle was confirmed by adjusting a sin function (with pedal rate, power and power/pedal rate ratio as variables) representing the evolution of pedal angle during the crank evolution to experimental data. The modifications due to power and pedal rate change that were observed in pedal kinematics were generally transferred to the upper joints of the legs.